Efeito de dois sistemas de manejo do solo nas propriedades físico-hídricas, desenvolvimento radicular e produtividade do milho - Silva, Marcelo Augusto de Aguiar e (2013)
Corn cultivation is part of crop rotation used by irrigation farmers from the southwestern region of São Paulo state, Brazil, who use no-tillage soil management as a kind of sustainable use of soil. The effect of this conservative practice on physical and hydrical properties of the soil, root development and corn crop yield compared to the conventional management was the objective of this work. The experiment was held at the Buriti-Mirim Farm, Angatuba, SP, Brazil, using an irrigated area with a center pivot system and two types of soil management: conventional and no-tillage systems. Although the no-tillage management had higher soil density and less water availability, no significant difference was found for both management systems concerning soil resistance to penetration, root development and crop yield. In both systems of soil management, 90% of roots were concentrated in the first 0-20cm of soil layer.